Earth System Studies in Northern Eurasia. Issue 16 (22nd April 2014) - Groisman, Pavel; Gulev, Sergey; Maksyutov, Shamil
<x xml:space="preserve">Abstract</x> During recent decades, northern Eurasia (north of 40°N and east of 15°E) was affected by unprecedented climate and environmental changes. Several droughts, including a heat wave in 2010 (that in European Russia may have been the cause of up to an additional 60, 000 deaths in July–August of that year, compared to the previous year; see http://ifaran.ru/science/seminars/Summer2010.html); alternated with hazardous extreme precipitation and flood events. Permafrost thaw, retreating Arctic sea ice, increasing areas of forest fire, and dramatic regional warming buffeted this region, tossing northern Eurasia from one extreme condition to the next.